Affect theory and autoethnography in ordinary information systems - Bødker, Mads; Chamberlain, Alan (2016)
This paper uses philosophical theories of affect as a lens for exploring autoethnographic renderings of everyday experience with information technology. Affect theories, in the paper, denote a broad trend in post-humanistic philosophy that explores sensation and feeling as emergent and relational pre- cognitive forces that impinge on a body and its capacity to act. A necessarily truncated account of af- fect theory, and three autoethnographic vignettes are presented to complement the philosophical ex- position and to provide reflections on possible empirical tactics for affective research in IS. Inspired by the challenges to IS reflected in Yoo’s notion of Experiential Computing, the paper contributes with examples of how everyday attentiveness to the senses can unveil new forms of embodiment related to ‘living with technology’. It suggests that feelings (both sensory visceral as well as more generalized moods) emerge out of intimate embodied entanglement with ubiquitous computing technologies infra- structures.